Predicting team rankings in basketball: The questionable use of on-court performance statistics - Ziv, G.; Lidor, R.; Arnon, M. (International Journal of Performance Analysis in Sport, 2010)
Statistics on on-court performances (e.g. free-throw shots, 2-point shots, defensive and offensive rebounds, and assists) of basketball players during actual games are typically used by basketball coaches and sport journalists not only to assess the game performance of individual players and the entire team, but also to predict future success (i.e. the final rankings of the team). The purpose of this correlational study was to examine the relationships between 12 basketball on-court performance variables and the final rankings of professional basketball teams, using information gathered from seven consecutive seasons and controlling for multicollinearity. Data analyses revealed that (a) some on-court performance statistics can predict team rankings at the end of a season; (b) on-court performance statistics can be highly correlated with one another (e.g. 2-point shots and 3-point shots); and (c) condensing the correlated variables (e.g. all types of shots as one category) can lead to more stable regressional models. It is recommended that basketball coaches limit the use of individual on-court statistics for predicting the final rankings of their teams. The prediction process may be more reliable if on-court performance variables are grouped into a large category of variables.